Dinâmica geoeconômica da indústria em Ampére-PR - Saggiorato, Bruno (2021)
Taking as a presupposition the complex Brazilian social formation, the country has a very large geographic heterogeneity. Thus, it is necessary to understand how the general processes are articulated, concretely and spatially, with regional Social-Spatial Formations (FSEs), and, from this, identify which attributes this combination generates, which new phenomena arise from this relationship, triggering geoeconomics differentiations between regions/municipalities. Therefore, this dissertation aims to understand the geoeconomics dynamics of the industry in Ampére, in its genesis, evolution and consolidation and also the main characteristics and determining factors of this process, understanding it not as an isolated fact, but in line with the regional and national context. The aim is also able to present an overview of the dynamics of the furniture sector in Brazil, a segment practically not studied in Geography. To comply with the proposal, the category of Social-spatial Training (FSE) was taken as a theoretical guide, added to bibliographical reviews on the subject, field work and a wide consultation and analysis of industrial and economic data. The FSE of Southwest Paraná, mesoregion where Ampére is located, is based on small commercial production. It was found that Ampére has a relevant manufacturing sector, standing out in two sectors of the manufacturing industry (clothing and furniture production). In the Southwest Paraná, it is the main hub of these sectors, in the state of Paraná it is among the top 10 hubs and in Brazil it is the 65th largest employer in the clothing sector and the 43rd in the furniture sector. This industrial importance is the result of the combination of private initiatives based on small commercial production, municipal public support and federal politics and programs that leveraged the internal market during the 2000s.